caracterização mecânica e estrutural de um dispositivo pdlc baseado em hidrogéis de paam e cristal líquido liotrópico LP/DeOH/H2O - Aouada, Fauze A. [UNESP]; De Moura, Marcia R. [UNESP]; Fernandes, Paulo R. G.; Rubira, Adley F.; Munizc, Edvani C. (My University, 2014)
MECHANICAL AND STRUCTURAL CHARACTERIZATION OF A PDLC DEVICE BASED ON PAAm HYDROGELS AND KL-DeOH-H2O LYOTROPIC LIQUID CRYSTAL. In this work, a novel device based on polyacrylamide (PAAm) hydrogels and KL-DeOH-H2O lyotropic liquid crystal (LLC), with potential for application as Polymer Dispersed Liquid Crystals (PDLC), was proposed and its properties characterized. The confinement of LLC promoted significant changes in spectroscopic, morphological, optical, hydrophilic, structural and mechanical properties due to the interaction between the LLC-PAAm matrix and entropic parameter changes. The mechanical and structural properties can be controlled by adjusting AAm, temperature and presence of LLC, which can be useful for technological applications of these systems in optical devices.
Mechanical and structural characterization of a PDLC device based on PAAm hydrogels and KL-DeOH-H2O lyotropic liquid crystal